Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/alcalc/agx084
|View full text |Cite
|
Sign up to set email alerts
|

Perfect for a Gin and Tonic: How Context Drives Consumption Within a Modified Bogus Taste Test

Abstract: In the absence of any pharmacological effects of alcohol, social and environmental context have an interactive impact on shaping consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…substance-related cues [9]) and internal factors such as stress [10,11] and craving [12,13], which can be difficult (both practically and ethically) to model in the laboratory. Similarly, individuals' substance use may be suppressed in contexts that are not typically associated with substance use; for example, Monk et al [16] demonstrated increased alcohol consumption during an experiment conducted in a pub compared to a library. For example, Monk et al [14] demonstrated that a greater number of alcoholic drinks were reported in real time using EMA than when assessed retrospectively (see also [15]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…substance-related cues [9]) and internal factors such as stress [10,11] and craving [12,13], which can be difficult (both practically and ethically) to model in the laboratory. Similarly, individuals' substance use may be suppressed in contexts that are not typically associated with substance use; for example, Monk et al [16] demonstrated increased alcohol consumption during an experiment conducted in a pub compared to a library. For example, Monk et al [14] demonstrated that a greater number of alcoholic drinks were reported in real time using EMA than when assessed retrospectively (see also [15]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Monk et al [14] demonstrated that a greater number of alcoholic drinks were reported in real time using EMA than when assessed retrospectively (see also [15]). Similarly, individuals' substance use may be suppressed in contexts that are not typically associated with substance use; for example, Monk et al [16] demonstrated increased alcohol consumption during an experiment conducted in a pub compared to a library. In relation to this, participants' expectations of drug effects may be suppressed in the laboratory, with self-reported alcohol outcome expectancies differing between typical drinking (pub) and atypical contexts (laboratory [17,18]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite not knowing the contents of a confederate's beverage, participants drank significantly more alcohol when a confederate drank alcohol, compared to when a confederate drank soda [88]. When in the presence of other people, participants also consumed more of what they believed was alcohol, but was actually a placebo, while in a pub environment compared to a library [89].…”
Section: Human Studiesmentioning
confidence: 90%
“…The outcomes are therefore measured in a more ecologically valid manner as compared to retrospective self-reports. This is of importance, since smoking behaviour is associated with mood and context [23,24]. Individuals may for instance smoke more during the weekend or on stressful days [31].…”
Section: Plos Onementioning
confidence: 99%
“…Effects of tDCS on addictive behaviour have often been measured with retrospective self-reports in the lab. Since craving and substance use are both episodic phenomena that are associated with affect and context [22][23][24], measuring these variables in daily life may lead to more reliable answers. Furthermore, retrospective measurements may be influenced by recall biases [25,26].…”
Section: Introductionmentioning
confidence: 99%